THE INFLUENCE OF JOB PROMOTION ON JOB SATISFACTION IN PT PUPUK SRIWIDJAJA PALEMBANG (CASE STUDY IN HUMAN RESOURCE DIVISION) - Karistya Safitri; zunaidah zunaidah; supardi A Bakri (JEMBATAN, 2018)
The purpose of this research is to learn and understand the effect of job promotion on job satisfaction in PT Pupuk Sriwidjaja Palembang. The object of this research is employee in Human Resource Division of PT Pupuk Sriwidjaja Palembang with 45 employees as sample. The sampling method used in this research is sensus method. The method used for collecting data is by questionnaire. The data collected are tested by validity test, reliability test, simple linear regression analysis, correletion coefficient (r) and determination coenfficient (R2) and t test by using SPSS version 22. The result of this research shows that job promotion has positive and significant effect to job satisfaction in PT Pupuk Sriwidjaja Palembang. Keywords : Job Promotion, Job Satisfaction